Differences in specific power performance among playing positions in top level female handball - Foretic, N.; Pavlinovic, V.; Spasic, M. (SportMont, 2022)
Since all activities in handball should be performed as fast and as powerful as possible, power is involved in almost all players` movements. There is an evident lack of studies that monitored this ability during matches. The study aimed to determine the situational differences in power among playing positions in top-level female handball. Variables included: body height, average game time, fastest shot, fastest sprint, and highest jump. Subjects were 227 female handball players that participated in the European handball championship 2020. Analysis of variance with the post-hoc Scheffe test was calculated. Results showed significant differences among playing positions in body height, fastest sprint and highest jump performed in real game situations. The largest differences were noticed in anthropometrics, with significant differences between back- and pivot-players on one side, and wing-players on the other. The fastest sprinting was recorded for wingers (26.5±1.12 km/h), who were significantly faster than other players. Jumping performance was most diverse among playing positions, with back-players being superior in this performance (47.24±17.61 cm, 48.44±20.71 cm, and 50.35±16.76 cm for centre-backs, leftbacks, and right-backs, respectively). Evidenced differences are explainable knowing the specific positions` roles and typical game situations which players encounter during the match.